2017
DOI: 10.1007/s12010-017-2649-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Bioactivity of the Anti-LOX-1 scFv Engineered by Multimerization Strategy

Abstract: Single-chain variable fragment (scFv) antibodies as therapeutic agents have the potential to reduce the production cost and immunogenicity relative to monoclonal antibodies, but their monovalency and lack of a fragment crystallizable region can lead to reduced function. Multimerization is one strategy for recovering the function; however, their application is limited by the production of multimeric proteins. In our previous study, an anti-lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) scFv sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Because oxidation levels increase robustly during systemic inflammatory diseases, the participation of ROS in pathological activity has been well accepted [54,55]. It has been reported that ROS can regulate gene expression and act as signaling molecules to modulate protein function [56][57][58][59][60][61]. H 2 O 2 and other reactive intermediates are involved in the expression of a number of proteins, such as cyclooxygenase-2 and prostaglandins [62,63], the proto-oncogenes c-jun, cfos, and c-myc [64], TRP ion channels [65], the vascular cell adhesion molecule-1, and intercellular adhesion molecule-1 [66,67], and also control the regulation of cell proliferation and survival, oncogene activation, immune response, apoptosis, and necrosis [67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Because oxidation levels increase robustly during systemic inflammatory diseases, the participation of ROS in pathological activity has been well accepted [54,55]. It has been reported that ROS can regulate gene expression and act as signaling molecules to modulate protein function [56][57][58][59][60][61]. H 2 O 2 and other reactive intermediates are involved in the expression of a number of proteins, such as cyclooxygenase-2 and prostaglandins [62,63], the proto-oncogenes c-jun, cfos, and c-myc [64], TRP ion channels [65], the vascular cell adhesion molecule-1, and intercellular adhesion molecule-1 [66,67], and also control the regulation of cell proliferation and survival, oncogene activation, immune response, apoptosis, and necrosis [67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…These scFvs exhibit specific binding affinity, enhanced bio-distribution, and low immunogenicity compared with humanized monoclonal antibodies, whilst being substantially cheaper to produce using bacterial expression systems. LOX-1-specific scFvs are in the early stages of development and ongoing studies are aiming to improve the binding affinity, thermostability, and serum half-life, and using multimerization techniques [ 172 , 173 ].…”
Section: Srs As Therapeutic Targets In Cvdmentioning
confidence: 99%